UJI KUALITAS TELUR AYAM RAS DI KOTA MANOKWARI - Kasmiati, .; Lumatauw, Sintje; Sumpe, Iriani (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2018)
A study was conducted to evaluate table eggs in Manokwari city. A total of 300 eggs were examined for external and internal qualities. The eggs were gathered from different places: local farmer for local eggs (1 respondent), markets for imported eggs (2 respondents)), supermarkets (4 respondents), egg distributors (1 respondent), and stalls (10 respondents)). The egg examinations were done twice, first was the time when no ship for egg transport came to Manokwari (period 1) to assume that the eggs had been kept for quite long before reached the consumers and second was the time when ship for egg transport that just arrived to Manokwari with the assumption that he eggs were still relatively fresh (periode 2). Results showed that the majority of table eggs in Manokwari had brown shells followed by spotted and light brown, all with oval shapes. Eggs gathered at period 2 were larger than those of period 1; local eggs were significantly heavier than imported eggs due to the difference of egg freshness. The local eggs of period 2 showed a very good air sac with AA quality, while the imported eggs had the air sac quality for A and B. The highest yolk score (8.88) were observed at local eggs at period 2.